Encoding human serine phosphopeptides in bacteria for proteome-wide identification of phosphorylation-dependent interactions. - Barber, Karl W; Muir, Paul; Szeligowski, Richard V; Rogulina, Svetlana; Gerstein, Mark; Sampson, Jeffrey R; Isaacs, Farren J; Rinehart, Jesse (Nature biotechnology, 2018)
Post-translational phosphorylation is essential to human cellular processes, but the transient, heterogeneous nature of this modification complicates its study in native systems. We developed an approach to interrogate phosphorylation and its role in protein-protein interactions on a proteome-wide scale. We genetically encoded phosphoserine in recoded E. coli and generated a peptide-based heterologous representation of the human serine phosphoproteome. We designed a single-plasmid library encoding >100,000 human phosphopeptides and confirmed the site-specific incorporation of phosphoserine in >36,000 of these peptides. We then integrated our phosphopeptide library into an approach known as Hi-P to enable proteome-level screens for serine-phosphorylation-dependent human protein interactions. Using Hi-P, we found hundreds of known and potentially new phosphoserine-dependent interactors with 14-3-3 proteins and WW domains. These phosphosites retained important binding characteristics of the native human phosphoproteome, as determined by motif analysis and pull-downs using full-length phosphoproteins. This technology can be used to interrogate user-defined phosphoproteomes in any organism, tissue, or disease of interest.
Keywords: *Peptides/ge [Genetics]; *Protein Interaction Maps/ge [Genetics]; *Proteome/ge [Genetics]; *Serine Proteases/ge [Genetics]; 14-3-3 Proteins; 14-3-3 Proteins/ch [Chemistry]; 14-3-3 Proteins/ge [Genetics]; 14-3-3 proteins; Amino Acid Motifs; Amino Acid Motifs/ge [Genetics]; Amino acids; Article; Binding characteristics; Cellular process; DNA library; Encoding (symbols); Enzyme activity; Escherichia coli; Escherichia coli/ge [Genetics]; Gene Library; Human proteins; Humans; Motif analysis; Peptides; Peptides/ch [Chemistry]; Phosphopeptides; Phosphoproteomes; Phosphorylation; Phosphoserine; Phosphoserine/ch [Chemistry]; Plasmids; Plasmids/ge [Genetics]; Protein Interaction Maps; Protein-protein interactions; Proteome; Serine Proteases; Serine Proteases/ch [Chemistry]; Signal encoding; WW Domains; WW Domains/ge [Genetics]; WW domain; amino terminal sequence; assay; carboxy terminal sequence; cell lysate; chemistry; controlled study; dept.bio; fluorescence activated cell sorting; fusion protein; gene library; genetics; high throughput sequencing; human; immunoblotting; immunoprecipitation; in vitro study; ligand binding; mass spectrometry; nonhuman; peer-reviewed; peptide; peptide library; phosphopeptide; phosphorylation; phosphoserine; plasmid; priority journal; protein 14 3 3; protein analysis; protein degradation; protein motif; protein phosphorylation; protein protein interaction; proteome; proteomics; pull down assay; serine; serine proteinase; transcription factor FKHRL1; transfer RNA

College community–based physical activity support at a public university during the COVID-19 pandemic: retrospective longitudinal analysis of intra- versus interpersonal components for uptake and outcome association - Ash, Garrett; Mak, Selene; Haughton, Adrian; Augustine, Madilyn; Bodurtha, Phillip; Axtell, Robert; Borsari, Beatrice; Liu, Jason; Lou, Shaoke; Xin, Xin; Fucito, Lisa; Jeon, Sangchoon; et al. (JMIR mhealth and uhealth, 2025)
Background College students are vulnerable to setting long-term trajectories of low physical activity (PA) but are reachable via mobile health fitness tracking (eg, mobile health step counting) and interpersonal support tailored to the college community. However, no studies have statistically isolated the appeal and influence of these intra- and interpersonal components in college-based PA interventions. Objective This study retrospectively examined a college-based PA promotion program at a northeast US public university during the COVID-19 pandemic to (1) test the impact of student status on the use of intervention components and (2) determine whether such use was associated with successful retention and goal achievement in the program. Methods The university used a commercial platform for a 30-day PA promotion program during April 2021 with intrapersonal (step-tracker syncing, education, self-monitoring, and motivational messaging) and interpersonal (friend interactions and team games) components. App use was operationalized as intrapersonal (frequency of opening app, education, and self-monitoring) and interpersonal (friends made in-app and team affiliation and size). Results Campus-wide emails elicited sign-up by 156 undergraduate students, 57 graduate students, and 126 faculty and staff members. Objective 1 yielded the following results: undergraduates used the app less frequently (median 0.8, IQR 0.4-1.7 times per day) than other groups (graduate students: median 1.4, IQR 0.7-2.7 times per day; P=.01; faculty: median 1.3, IQR 0.7-2.7 times per day, H2=14.5; P=.001) but made the same number of friends (median 1-2) and teammates (median 8-9; P=.77 for friends and P=.93 for teammates). Objective 2 yielded the following results: most participants (313/335, 93.4%; 95% CI 90%-96%) were retained for the first 7 days, but by 30 days, retention dropped, most notably for undergraduate students (82/154, 53.2%; 95% CI 45%-61%), followed by graduate students (39/56, 70%; 95% CI 56%-81%) and faculty and staff (93/125, 74.4%; 95% CI 66%-82%; χ22=12.6; P<.001). Retention was associated with app engagement frequency (model hazard ratio 0.56, 95% CI 0.43-0.72; P<.001) and affiliation with a team having high median app engagement and a large size (intracluster correlation coefficient 0.064, 95% CI 0.001-0.164, P=.05). Meeting a daily step goal was associated with app engagement frequency (β=.72, SE=0.21; P=.001), number of friends (β=.40, SE 0.20; P=.04), and an initial motive of maintaining or increasing (rather than starting) PA (β=.99, SE=0.21; P<.001). Conclusions College students, compared with faculty and staff, used the app less frequently, used the app for a shorter duration before abandonment, and met the step goal on fewer days. Engagement with the program was associated with longer retention and better PA outcomes, which were critically modified by the interpersonal engagement. These findings suggest that college students using virtual PA support during times of physical isolation could benefit from more tailored implementation strategies (eg, timed prompts and team reassignments).
Keywords: Computer science; Coronavirus disease 2019 (COVID-19); Demography; Disease; Gerontology; Infectious disease (medical specialty); Internal medicine; Medicine; Preprint; Sociology; dept.hms

Establishing a global standard for wearable devices in sport and fitness: Perspectives from the new england chapter of the american college of sports medicine members. - Ash, Garrett I.; Stults-Kolehmainen, Matthew A.; Busa, Michael A.; Gregory, Robert; Garber, Carol Ewing; Liu, Jason; Gerstein, Mark; Casajús, José A.; González-Agüero, A.; Constantinou, Demitri; Geistlinger, Michael; Guppy, Fergus M.; et al. (Current sports medicine reports, 2020)
The recent explosion of wearable technology and the associated concerns prompted the International Federation of Sports Medicine (FIMS) to create a quality assurance standard for wearable devices, which provides commissioned testing of marketing claims and endorsement of commercial wearables that test favorably. An open forum as announced in the conference advertising was held at the Annual Meeting of the New England Regional Chapter of the American College of Sports Medicine (NEACSM) November 7 to 8, 2019, in Providence, Rhode Island, USA for attending NEACSM members to voice their input on the process. Herein, we report the proceedings. The round table participants perceived the quality assurance standard to be important, but identified some practical process challenges that included the broad scope and complexity of the device universe, the need for a multiphase testing pathway, and the associated fees for product evaluation. The participants also supported the evaluation of device data analysis, behavioral influences, and user experience in the overall evaluation. Looking forward, the FIMS quality assurance standard faces the challenge of balancing these broader perspectives with practical constraints of budget, facilities, time, and human resources. © 2020 by the American College of Sports Medicine.
Keywords: Fitness Trackers; Humans; New England; Sports; Sports Medicine; United States; Wearable Electronic Devices; activity tracker; adult; article; budget; cosmos; data analysis; dept.hms; electronic device; human; peer-reviewed; quality control; sport; sports medicine

Establishing a global standard for wearable devices in sport and exercise medicine: Perspectives from academic and industry stakeholders - Ash, Garrett I.; Stults-Kolehmainen, Matthew; Busa, Michael A.; Gaffey, Allison E.; Angeloudis, Konstantinos; Muniz-Pardos, Borja; Gregory, Robert; Huggins, Robert A.; Redeker, Nancy S.; Weinzimer, Stuart A.; Grieco, Lauren A.; Lyden, Kate; et al. (Sports medicine (Auckland, N.Z.), 2021)
Millions of consumer sport and fitness wearables (CSFWs) are used worldwide, and millions of datapoints are generated by each device. Moreover, these numbers are rapidly growing, and they contain a heterogeneity of devices, data types, and contexts for data collection. Companies and consumers would benefit from guiding standards on device quality and data formats. To address this growing need, we convened a virtual panel of industry and academic stakeholders, and this manuscript summarizes the outcomes of the discussion. Our objectives were to identify (1) key facilitators of and barriers to participation by CSFW manufacturers in guiding standards and (2) stakeholder priorities. The venues were the Yale Center for Biomedical Data Science Digital Health Monthly Seminar Series (62 participants) and the New England Chapter of the American College of Sports Medicine Annual Meeting (59 participants). In the discussion, stakeholders outlined both facilitators of (e.g., commercial return on investment in device quality, lucrative research partnerships, and transparent and multilevel evaluation of device quality) and barriers (e.g., competitive advantage conflict, lack of flexibility in previously developed devices) to participation in guiding standards. There was general agreement to adopt Keadle et al.’s standard pathway for testing devices (i.e., benchtop, laboratory, field-based, implementation) without consensus on the prioritization of these steps. Overall, there was enthusiasm not to add prescriptive or regulatory steps, but instead create a networking hub that connects companies to consumers and researchers for flexible guidance navigating the heterogeneity, multi-tiered development, dynamicity, and nebulousness of the CSFW field. © 2021, The Author(s), under exclusive licence to Springer Nature Switzerland AG.
Keywords: Consensus; Exercise; Humans; Sports; Sports Medicine; United States; Wearable Electronic Devices; adult; article; consensus; consumer; data science; dept.hms; electronic device; exercise; female; human; human experiment; investment; major clinical study; male; sport; sports medicine